2004
DOI: 10.1152/ajprenal.00269.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, renal infiltration of immune cells, and salt-sensitive hypertension: all for one and one for all

Abstract: Recent evidence indicates that interstitial infiltration of T cells and macrophages plays a role in the pathogenesis of salt-sensitive hypertension. The present review examines this evidence and summarizes the investigations linking the renal accumulation of immune cells and oxidative stress in the development of hypertension. The mechanisms involved in the hypertensive effects of oxidant stress and tubulointerstitial inflammation, in particular intrarenal ANG II activity, are discussed, focusing on their pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
228
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(249 citation statements)
references
References 157 publications
16
228
0
5
Order By: Relevance
“…8 However, subsequent studies suggested that immune cell infiltration in the kidney may be the cause, not the result, of hypertension in this model. Indeed, in nearly all models of salt-sensitive hypertension, the tubulointerstitium of rat kidneys are infiltrated with lymphocytes and macrophages, 9,10 and a correlation between the intensity of the inflammatory cell infiltration and the severity of the blood pressure elevation was apparent. 11 In experimental models of hypertension, monocyte/macrophage infiltration of the perivascular fat renal tissue, as well as vascular adventitia, was observed.…”
Section: Experimental Data and Possible Pathways For Inflammation-indmentioning
confidence: 99%
“…8 However, subsequent studies suggested that immune cell infiltration in the kidney may be the cause, not the result, of hypertension in this model. Indeed, in nearly all models of salt-sensitive hypertension, the tubulointerstitium of rat kidneys are infiltrated with lymphocytes and macrophages, 9,10 and a correlation between the intensity of the inflammatory cell infiltration and the severity of the blood pressure elevation was apparent. 11 In experimental models of hypertension, monocyte/macrophage infiltration of the perivascular fat renal tissue, as well as vascular adventitia, was observed.…”
Section: Experimental Data and Possible Pathways For Inflammation-indmentioning
confidence: 99%
“…We have raised the possibility that autoimmune reactivity could be responsible for the low-grade tubulointerstitial inflammation in the kidney that, in concert with local angiotensin II generation and oxidative stress, would provide the critical intrarenal milieu that would favor the chronic impairment in pressure natriuresis that underlies SSHTN. 74 Previous studies that examined the immune reactivity in hypertension have given conflicting results. In contrast with the experimental data that indicate that suppression of the immune system ameliorated hypertension, Tuttle and Boppana 75 reported that interleukin 2 had antihypertensive effects and it was suggested that activation of the immune system could be an adaptive response directed to suppress what otherwise could be life-threatening increments in blood pressure.…”
Section: Immune Reactivity and Hypertensionmentioning
confidence: 99%
“…10,11 In the past decade, inflammation and oxidative stress have emerged as major players in vascular remodeling of hypertension in addition to known mechanisms, such as salt sensitivity, insulin resistance, and an imbalance in the renin-angiotensin system. 12 -15 Polymorphonuclear leukocytes (PMNL) are the main producer of reactive oxygen species (ROS) and have been shown to be involved in hypertension in both human and animal models.…”
Section: Essential Hypertension (Eh [Min1455]mentioning
confidence: 99%